Automatic compositional verification of timed systems - LIN, Shang-Wei (Institutional Knowledge at Singapore Management University, 2012)
Specification and verification of real-time systems are important research topics with crucial applications; however, the so-called state space explosion problem often prevents model checking to be used in practice for large systems. In this work, we present a self-contained toolkit to analyze real-time systems specified using event-recording automata (ERAs), which supports system modeling, animated simulation, and fully automatic compositional verification based on learning techniques. Experimental results show that our tool outperforms the state-of-the-art timed model checker.